Interplay between autophagy and metacyclogenesis in Trypanosoma cruzi, unravelling the role of TcVps34-Vps15 complex - Leis, Juan Manuel (2023)
Autophagy is a ubiquitous eukaryotic process that also occurs in trypanosomatid parasites. Half of the known yeast and mammalian AuTophaGy (ATG) proteins were detected in trypanosomatids, although with low sequence conservation. Interestingly, autophagy is involved in differentiation of T. cruzi from epimastigotes to metacyclic trypomastigotes, a process called metacyclogenesis. In mammals, two kinases differentially regulate the process of autophagy: mTor and a phosphatidylinositol 3-kinase, Vps34, which interact with a regulatory subunit, Vps15. In this work, we demonstrate that parasites overexpressing TcVps34 or TcVps15 proteins enhance both, autophagy and metacyclogenesis. TcVps34 or TcVps15 overexpressing epimastigotes were able to differentiate to metacyclic forms in a higher proportion than wild type cells. Parasites overexpressing these proteins showed a more intense labeling with the autophagosome marker Atg8.1 and higher levels of monodansycadaverine (MDC) staining, a specific in vivo marker for autophagic vacuoles, in the intermediate forms of differentiated parasites, in comparison to control parasites. To extend this study we also performed assays with DQ-BSA, to evaluate degradative compartments. TcVps34 and TcVps15 overexpressing epimastigotes subjected to nutritional stress shown a significant increase in the number of lysosomes, as compared to controls. In addition, treatment with wortmannin, an inhibitor of autophagy, of parasites exposed to differentiation conditions impaired the autophagic response in less measure in overexpressing parasites. Finally, we are performing infection assays with these overexpressing parasites to assess whether this process is affected. Taken together, these data demonstrate the key role of phosphatidylinositol 3-phosphate pathway in autophagy, differentiation and cell cycle progression in T. cruzi.